Past and present bacterial communities in deglaciating northern latitude catchments reveal varied soil carbon sequestration potential - Akhmetkaliyeva, Saule; Dean, Andrew P.; Clarke, Leon J.; Cook, Simon J.; Lopez, Sharon Ruiz; Sparkes, Robert B. (Science of The Total Environment, 2025)
Glacier retreat in northern latitudes exposes new landscapes that may develop soils and ecosystems, which in turn may sequester carbon and serve as a negative climate change feedback. Proglacial soil development and landscape evolution were investigated using transects from three high-latitude glacial systems (Tarfala, Sweden; Vatnajökull, Iceland; Zackenberg, Greenland). Soil samples were analysed for organic carbon (OC) concentration, bacteriohopanepolyol biomarkers (BHPs, membrane lipids that trace major microbial groups), and 16S rRNA gene sequencing. Soil and sediment samples from Sweden showed lower OC concentrations (0.27 ± 0.26 wt%) than deposits from Iceland (1.59 ± 2.12 wt%) and Greenland (1.62 ± 1.54 wt%). Highest OC concentrations were from moraines exposed for several millennia, while recently deglaciated areas in Sweden and Iceland had the lowest OC values. Higher fractional abundance of soil-specific BHPs down-valley (up to 30 % in Greenland), and matching increases in the R' soil index (up to 0.37 in Greenland), suggest soils are gradually developing in recently deglaciated areas, with a stable soil microbial community observed in some soils from Iceland and Greenland. Microbial communities stabilized quickly, adapting to the new environment. Acidobacteria, Actinobacteria, Chloroflexi, Proteobacteria, Planctomycetes, and Verrucomicrobia were the most relatively abundant phyla identified in deglaciated areas, while candidate phylum Dormibacteraeota had high concentrations in samples from Sweden. Linking organic biomarkers with bacterial communities suggests that soil-marker BHPs were produced by Rhodospirillaceae and may have been produced by Bradyrhizobiaceae and Hyphomicrobiaceae. However, despite some similarities in microbial communities, differences in soil development suggest that the evolution of deglaciating landscapes and their impact on the global carbon cycle may vary substantially.